Digital Promotion Effectiveness Of Hydroponic Products On Instagram: Evidence From Pontianak - Ellyta; Agustina Gafvi, Hilaria; Dominikus Bancin, Hardi (JURNAL AGRIBISAINS, 2026)
Digital promotion via Instagram is increasingly vital for agribusiness, yet the simultaneous effects of content quality, brand image, and trust on promotion effectiveness remain underexplored for hydroponic products. This study examines causal relationships among content quality (X₁), brand image (X₂), trust (X₃), and digital promotion effectiveness (Y) at Hidroponti, a hydroponic enterprise in Pontianak. Using a quantitative explanatory design, 150 respondents were selected through purposive sampling and analyzed via PLS-SEM using SmartPLS 3.0. Brand image (β = 0.847; p < 0.001) emerged as the dominant predictor, followed by content quality (β = 0.271; p < 0.001), while trust showed a significant negative effect (β = −0.184; p < 0.001). The model achieved R² = 0.847. Managerially, hydroponic businesses should prioritize consistent brand image investment, enhance content quality, and differentiate promotional strategies between new and loyal consumer segments to maximize Instagram promotion effectiveness.